The armchair birder : discovering the secret lives of familiar birds - Yow, John (University of North Carolina Press, 2009)
Bird lovers, take heart! While the birding literature is filled with tales of expert observers spotting rare species in exotic locales, John Yow's The Armchair Birder is here to remind us that the most fascinating birds can be the ones perched right outside our windows. In thirty-five engaging, humorous, and even irreverent essays, Yow reveals the fascinating lives of birds you probably already recognize and naturally want to know more about, because they're the ones you see nearly every day. Following the seasons of the year, Yow covers forty-two species, from the Carolina wren that rings in.